Comparison between Robotic Assisted Gait Training and Conventional Gait Training in Stroke Patients: A Randomized Controlled Trial - ม่วงเงิน มณฑิชา; โลหารชุน บุษกร; วรฤทธานนท์ ชุติภา; ศัตรูพินาศ ณัฐชา; สายพันธ์ ภคอร; แก้วสว่าง สาริณี (Journal of Health Science of Thailand, 2022)
The objective of this study was to compare between robotic-assisted gait training and conventional gait training in stroke patients. The study design was a randomized controlled trial. The samples were 18-75 years stroke patients with the first stroke that had symptoms of the disease for more than 1 month up to the date of the study but not more than 1 year, able to walk with the Functional Ambulatory Category (FAC) ≥2. The participants were divided into 2 groups: the experimental group and the control group. Both groups received the same basic exercise for 30 minutes after that the experimental group received robotic-assisted gait training for 30 minutes while the control group received gait training on flat ground by a physical therapist for 30 minutes. Training was performed 3 times a week for 4 weeks, 12 sessions in total. The statistics analysis was performed by using descriptive statistics, and comparing data differences between the experimental group and the control group by using independent t-test and Mann Whitney U test. As for the results, there were 62 subjects who participated in full 4 weeks (31 persons in each group). It was found that there was no statistically significant difference on the main measure; the gait speed, the second; the balance by the Berg balance scale (BBS), the level of recovery of stroke patients by the National Institute of Health Stroke Scale, Thai version (NIHSS-T) and Functional Ambulatory Classification (FAC) between the 2 groups (p>0.05). From the results of the study, it was concluded that between walking training with robotic-assisted gait training and conventional gait training, there were no differences in walking speed, balance and walking ability.